Sport and physical education in China - Riordan, James, 1936-2012; Jones, Robin (Robin E.) (ISCPES book series., 1999)
Anyone wishing to gain an insight into the PE and sporting experiences of Chinese citizens both in historical and contemporary society will find this book essential reading.